Intellectual capital - Brooking, Annie. (International Thomson Business Press, 1997)
The third millennium enterprise. The emergence of intellectual capital. Market assets. Intellectual property assets. Human-centred assets. Infrastructure assets. Planning an intellectual capital audit...